Use of a Novel Couples' Verification Tool in a Male Partner Treatment Study of Women With Recurrent Bacterial Vaginosis. Issue 12 (December 2020) - Muzny, Christina A.; Pontius, Angela; Woznicki, Nicole; Hudak, Kathryn E.; Lensing, Shelly Y.; Sobel, Jack D.; Schwebke, Jane R.
Abstract : Abstract: Verification of relationship status beyond self-report is an important aspect in sexually transmitted infection research, including partner treatment studies where primary sexual partners are targeted for enrollment. This exploratory study describes the use of a novel couples' verification tool in a male partner treatment study of women with recurrent bacterial vaginosis. Abstract : This study describes the use of a novel couples' verification tool in a male partner treatment study of women with bacterial vaginosis.Supplemental digital content is available in the text.